2012
DOI: 10.1155/2012/932847
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Postural Restrictions after BPPV Treatment: Real Effect on Successful Treatment and BPPV’s Recurrence Rates

Abstract: Background. Canalith repositioning techniques are adequately established in the literature, as the treatment of choice for benign paroxysmal positional vertigo. However, the role of the posttreatment instructions is still not clearly defined.Patients and Methods. A retrospective chart review of 82 patients was conducted in order to determine the efficacy of postural restrictions, when combined with the classic canalith repositioning techniques, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…The results of our study are not surprising, as they are more or less in accordance with the current literature. Our findings agree with most of the previous studies (DeBoodt, 2003;Radtke et al, 2004;Roberts et al, 2005;Fyrmpas et al, 2009;De Stefano et al, 2011;Papacharalampous et al, 2012;Toupet et al, 2012) that investigated the efficacy of postural restrictions on the success rate of CRM and reported that these restrictions do not influence resolution of BPPV. In addition, most of the patients in the restricted groups expressed a serious sense of discomfort.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study are not surprising, as they are more or less in accordance with the current literature. Our findings agree with most of the previous studies (DeBoodt, 2003;Radtke et al, 2004;Roberts et al, 2005;Fyrmpas et al, 2009;De Stefano et al, 2011;Papacharalampous et al, 2012;Toupet et al, 2012) that investigated the efficacy of postural restrictions on the success rate of CRM and reported that these restrictions do not influence resolution of BPPV. In addition, most of the patients in the restricted groups expressed a serious sense of discomfort.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, there are contradictory reviews on the need for involvement of postmaneuver restrictions as a part of the treatment protocol for BPPV (Fyrmpas et al, 2009;De Stefano et al, 2011;Papacharalampous et al, 2012), which are used in an effort to prevent the otoconial debris from returning to the semicircular canals after treatment. Cakır et al (2006) and McGinnis et al (2009) stated positive outcomes for these restrictions.…”
mentioning
confidence: 99%
“…All the patients in our study are instructed with the postural restriction (avoid sudden head movements and lying on their affected side) in at least three days after the CRM, in order to prevent canalith from going back to the affected canal. There are some reports that show postural restrictions appeared significant as a post-treatment instruction [15], while some others show it did not affect the outcomes of CRM, as well as the recurrence rate [16]. There are also some reports about canal conversions after reposition.…”
Section: Discussionmentioning
confidence: 99%
“…The patients sleeping on their affected side after the repositioning maneuver had a higher recurrence rate than patients with other sleep positions. However, other studies did not find an effect of postural restrictions on recurrence of BPPV [14][16], [18], [22]. Another study showed that the time course in remission of positional vertigo is not affected by the head-lying side during sleep [31].…”
Section: Discussionmentioning
confidence: 97%